Effectiveness of Liquid Probiotics from Organic Waste to Treat Hotel Domestic Waste - Jahruddin Jahruddin; Badrus Zaman; Sri Sumiyati (Fakultas Teknik, 2022)
With the hotel business rapidly growing, the emergence of pollution is increasing from year to year, including wastewater. Several processes are available to treat domestic wastewater. One of the biological processes that will be used is by using probiotics. This study aims to analyze the effectiveness of liquid probiotics from organic waste to treat domestic wastewater. The parameters observed in this study were PH, BOD5, COD, TSS, oil and fat, ammonia, and total coliform. In this study, two types of treatment were applied, namely treatment I (liquid waste only) and treatment II (probiotics + wastewater from the WWTP aeration process). The volume of the wastewater is varied in treatment II. The mixing contact times used were 24 hours, 42 hours, and 72 hours. The best result is seen in Ammonia with 24 hours of aeration of wastewater and a mixture of 150 ml/liter probiotics. The improvements that meet the government's threshold value (TLV) are total coliforms in experiments with wastewater aeration for 42 hours and a mixture of 100 ml/liter probiotics. The total coliforms improvement was seen in the 72-hour aeration experiment of wastewater and a mixture of 100 ml of probiotics.